2019
DOI: 10.1021/acs.langmuir.9b02928
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of CO Binding Sites on Stepped Pt Single Crystal Electrodes in Alkaline Solutions by in Situ FTIR Spectroscopy

Abstract: The site geometry preference of CO binding on stepped Pt single crystals in alkaline solution was investigated by in situ FTIR spectroscopy. The surfaces of the Pt single crystals consisted of different width (111) terraces, interrupted by ( 110) or (100) monoatomic steps.Experiments carried out with CO adsorbed exclusively on the top of the steps revealed that only linearly bonded CO formed on the (110) steps, while two CO binding geometries (linear and bridge) were observed on the (100) steps. On one hand, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 72 publications
(145 reference statements)
2
12
0
Order By: Relevance
“…Our calculated results agree well with the experimental data from Farias et al under electrochemical conditions where Pt(322) and Pt(311) surfaces, that present a (100) step, show a large amount of bridge site CO on their terraces, while Pt(332) and Pt(331) surfaces, with a (111) step, show a very large majority of top site CO. 32 They also agree with the UHV experiments of Tränkenschuh et al in the case of Pt(553)). 24 The kink surface (Pt(643)) shows a different type of arrangement where CO aligns parallel to the step edge.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Our calculated results agree well with the experimental data from Farias et al under electrochemical conditions where Pt(322) and Pt(311) surfaces, that present a (100) step, show a large amount of bridge site CO on their terraces, while Pt(332) and Pt(331) surfaces, with a (111) step, show a very large majority of top site CO. 32 They also agree with the UHV experiments of Tränkenschuh et al in the case of Pt(553)). 24 The kink surface (Pt(643)) shows a different type of arrangement where CO aligns parallel to the step edge.…”
Section: Discussionsupporting
confidence: 87%
“…On Pt(335) at 0.5 ML coverage, EELS also shows that all edge sites are occupied with top CO, while on the terrace half of the sites are occupied with a 2:1 top-to-bridge ratio. 26 In situ FTIR studies in solution and electrochemical conditions indicates that the preferred binding mode of CO on the terrace of stepped surfaces with short terraces depends on the type of step: surfaces with (100) steps (Pt(322) and Pt(311)) show a large amount of bridge site CO on their terraces, while those with (111) steps (Pt(332) and Pt(331)) mostly provide top site CO. 32 This suggests an interesting mechanism, of unknown origin to our knowledge, by which the type of step can control the binding site of CO on the terraces.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it was observed that the position of the COads band in the in situ FTIR spectra is insensitive to the step density, suggesting that inter-molecular coupling is restricted to COads species along a line of steps [41]. For comparison, Figure 3 To determine the effect of the CO traces on the stripping voltammogram, the experiments in Figure 4 were repeated using a purging time for elimination of the nonadsorbed CO of 10 minutes (Figure 5).…”
Section: Voltammetric Profiles Of the Electrodes In A Co-free Electrolytementioning
confidence: 99%